Sex-Differences in Oral Anticoagulant-Related Intracerebral Hemorrhage - Grundtvig, Josefine; Ovesen, Christian; Steiner, Thorsten; Carcel, Cheryl; Gaist, David; Christensen, Louisa; Marstrand, Jacob; Meden, Per; Rosenbaum, Sverre; Iversen, Helle K.; Kruuse, Christina; Christensen, Thomas; et al. (Frontiers in Neurology, 2022)
Introduction and aim: Data remain limited on sex-differences in patients with oral anticoagulant (OAC)-related intracerebral hemorrhage (ICH). We aim to explore similarities and differences in risk factors, acute presentation, treatments, and outcome in men and women admitted with OAC-related ICH Method: This study was a retrospective observational study based on 401 consecutive patients with OAC-related ICH admitted within 24 hours of symptom onset. The study was registered on osf.io. We performed logarithmic regression and cox-regression adjusting for age, hematoma volume, Charlson Comorbidity Index (CCI) and pre-stroke modified Ranking Scale (mRS). Gender and age were excluded from CHA2DS2-VASc and CCI was not adjusted for age. Results: A total of 226 men and 175 women were identified. More men were pre-treated with vitamin K-antagonists (73.5 % men vs. 60.6 % women) and more women with non-vitamin K-antagonist oral anticoagulants (26.5 % men vs. 39.4 % women), p = 0.009. Women were older (mean age 81.9 years vs. 76.9 years, p < 0,001). CHA2DS2-VASc and CCI were similar in men and women. Hematoma volumes (22.1 mL in men and 19.1 mL in women) and NIHSS scores (13 vs 13) were not statistically different, while median Glasgow Coma Scale (GCS) was lower in women, (14 (8;15) vs 14 (10;15) p = 0.003). Women’s probability of receiving reversal agents was significantly lower (adjusted odds ratio (aOR) = 0.52, p = 0.007) but not for surgical clot removal (aOR = 0.56, p = 0.25). Women had higher odds of receiving do-not-resuscitate orders (DNRs) within a week (aOR = 1.67, p = 0.04). There were no sex-differences in neurological deterioration (aOR 1.48, p = 0.10), ability to walk at three months (aOR = 0.69, p = 0.21) or one-year mortality (adjusted hazard ratio = 1.18, p = 0.27). Conclusion: Significant sex-differences were observed in age, risk factors, access to treatment, and DNRs while no significant differences were observed in comorbidity burden, stroke severity, or hematoma volume. Outcomes including adjusted mortality, ability to walk, and neurological deterioration were comparable. This study supports the presence of sex-differences in risk factors and care but not in presentation and outcomes.